2009
DOI: 10.1007/s00436-009-1578-7
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of the essential oil of Cymbopogon citratus and its major component (citral) on Leishmania amazonensis

Abstract: Leishmaniasis causes considerable mortality throughout the world, affecting more than 12 million people. Cymbopogon citratus (DC) Stapf, Family Poaceae, is a widely used herb in tropical countries and is also known as a source of ethnomedicines. In this study, the inhibitory effect and the morphological and ultrastructural alterations on Leishmania amazonensis by the essential oil (EO) of C. citratus and its main constituent, citral, were evaluated. The results showed that the antiproliferative activity of EO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
61
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(70 citation statements)
references
References 24 publications
5
61
0
4
Order By: Relevance
“…Indeed, studies have demonstrated the in vitro activity of this essential oil against C. deanei, with mean IC 50 values for symbiont-bearing and symbiont-free strains of 120 and 60 μg/mL, respectively (Pedroso et al 2006). Interestingly, L. amazonensis promastigotes were more sensitive to the essential oil and citral, with IC 50 of about 1.7 and 8.0 μg/mL, respectively, after 72 h of incubation (Santin et al 2009). One study showed that 3.1 µM concentrations of neral or geranial (isomers of citral) were effective against epimastigotes of T. cruzi (Saeidnia et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, studies have demonstrated the in vitro activity of this essential oil against C. deanei, with mean IC 50 values for symbiont-bearing and symbiont-free strains of 120 and 60 μg/mL, respectively (Pedroso et al 2006). Interestingly, L. amazonensis promastigotes were more sensitive to the essential oil and citral, with IC 50 of about 1.7 and 8.0 μg/mL, respectively, after 72 h of incubation (Santin et al 2009). One study showed that 3.1 µM concentrations of neral or geranial (isomers of citral) were effective against epimastigotes of T. cruzi (Saeidnia et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This essential oil has been shown to be effective against protozoa and significantly reduced the growth of Plasmodium berghei (Tchoumbougnang et al 2005), the insect trypanosomatid Crithidia deanei (Pedroso et al 2006), L. amazonensis (Santin et al 2009) and all three evolutive forms of T. cruzi (Santoro et al 2007a).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In most cases, these plants are used without any scientific base. In the last years, several works showed the leishmanicidal effect of some Brazilian plant extracts or essential oils (Santin et al 2009, Albernaz et al 2010, Alviano et al 2012, Brito et al 2013. In a previous work, we reported the antileishmanial activity of extracts of 20 plants from the Brazilian flora (Braga et al 2007).…”
Section: Introductionmentioning
confidence: 85%
“…Kaffir lime possesses antioxidant, antimicrobial, antibacterial properties and the major compounds are sabinene, β-pinene, limonene, α-pinene, camphene, myrcene, terpinen-4-ol, α-terpineol, linalool, terpinolene and citronellal [10][11][12]. The main compounds in the essential oil of lemongrass are the monoterpene citral, a mixtures of the stereisomers geranial , neral and β-myrcene and antioxidant properties has also been reported [13,14]. Tamarind extract owns antioxidant and anti-inflammatory properties [15,16].…”
Section: Introductionmentioning
confidence: 99%